Reproductive behaviour and determinants in a low-fertility era in China. Issue 2 (4th May 2019) - Zheng, Zhenzhen
ABSTRACT: This commentary reviews low fertility in China and suggests a macro-micro approach to analyse reproductive behaviour and determinants. As there are more discouraging factors to childbirth in concurrent Chinese society then encouraging ones, the low fertility is more likely to stay, unless there are more specific and effective strategies to support couples fulfilling their childbearing desire.